Strategi Profesionalisme Guru PAUD Abad 21 dalam Menstimulasi Kemampuan Membaca Anak Usia Dini - David Triatna; Khamim Zarkasih Putro (Universitas Islam Tribakti Lirboyo Kediri, 2024)
21st-century ECE teachers face challenges in developing effective strategies to stimulate early reading abilities in children. This study aims to explore the strategy of 21st-century early childhood education (ECE) teachers' professionalism in stimulating early reading skills in young children focusing on the effectiveness of these strategies in enhancing children's interest and reading abilities. The study employs a descriptive qualitative research method, with two teachers from groups B1 and B2 of TK Piri Nitikan as the subjects. The findings highlight that the professionalism of 21st-century ECE teachers, particularly in using conventional picture storybooks and digital flipbooks, positively contributes to enhancing early reading skills. Conventional picture storybooks aid in developing fine motor skills and basic language abilities in children, while digital flipbooks offer a more interactive and engaging learning experience. Combining conventional and digital approaches in 21st-century ECE professionalism provides a strong foundation for improving early childhood reading abilities.